Science-design loop for the design of resilient urban landscapes - Salliou, Nicolas; Arborino, Tony; Nassauer, Joan Iverson; Salmeron, Diego; Urech, Philipp; Vollmer, Derek; Grêt-Regamey, Adrienne (Socio-Environmental Systems Modelling, 2023)
Urban landscapes face significant challenges, as they must transform towards sustainability while remaining resilient. Urban landscape transformation is a complex task for landscape designers. They must not only create new solutions for landscapes but also ensure that their proposals are capable to deliver and maintain key ecosystems services over time and especially after shocks. In practice, designers must increase their dialogue with scientists and engineers to include expertise on ecosystems functions and services. Through science-design feedback loops, designers can be challenged by scientists’ models and simulations and thus create informed designs. Lastly, stakeholders also catalyse key steps of such a process, in particular by providing local expertise as well as co-constructing and validating the informed designs. In this paper, we introduce a roadmap, centred on an intensive interdisciplinary dialogue – a science-design loop. We illustrate the relevance of this roadmap with the analysis of five case studies about flood management and blue-green infrastructures. We analyse them according to the main steps of our roadmap and with the support of key interviews with experienced practitioners. First, this analysis provides an overview of best practices and challenges in the current urban landscape design world. But above all, we show the relevance of the proposed roadmap to muster science and design in a balanced manner in urban transformations.